Manajemen Sumber Daya Manusia dalam Pendidikan Islam (Studi Kasus di SD Plus Lillah Pasir Putih) (Indo-MathEdu Intellectuals Journal, 2024)
This research will explain related to the concept of human resource management in Islamic education. The study used descriptive qualitative methods implemented by collecting data obtained from documentation, observation, and interviews. The results showed that SD Plus Lillah Pasir Putih meets the needs of teachers / educators and education staff in accordance with needs such as administrative personnel, cleanliness, and security. HR competencies are enhanced through education and training, seminars, workshops, and internships. Recruitment and selection of HR candidates is carried out every year since its establishment, along with the development of the school and the increase in the number of students. Meanwhile, compensation, both financial and non-financial, is always improved to provide qualified quality human resources. The implementation of Islamic Education Human Resources in Plus Lillah Pasir Putih has been well implemented, especially in the field of HR management, ranging from HR planning, recruitment, selection of HR candidates, training, and development, to employee relations